Customer satisfaction level and operating process of City Brokerage Limited : Nikunja branch - Rahman, Md. Mizanur (BRAC University, 2013)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.